Innovative Targets in Deep Brain Stimulation: Advancing Neurosurgical Treatment of Movement Disorders - Samy Hassanen Mohamed, Magdy El-Sayed Hassan Rashed , Amr Mohamed Mohamed El Bakry, Ahmed El-Shabrawy Sweilam, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Background: Deep brain stimulation (DBS) has revolutionized the management of movement disorders such as Parkinson's disease, essential tremor, and dystonia by targeting well-established structures like the subthalamic nucleus (STN), globus pallidus internus (GPi), and ventral intermediate nucleus (VIM) of the thalamus. Despite the substantial symptomatic relief these conventional targets offer, limitations related to adverse effects and incomplete symptom control have prompted the exploration of novel DBS targets aimed at improving therapeutic outcomes.